Potential for biogas production of durian peels by the solid-state anaerobic digestion process - Markphan, Wattananarong; Chaisorn, Wilaiwan; Pimsan, Rungnapa; Kuyyogsuy, Arnannit (Srinakharinwirot University Journal of Sciences and Technology, 2025)
The purpose this research is to study the Physical, Chemical components and possibility of using the peels of five different durian species Montong (MT), Chanee (CN), Kanyao (KY), Ban 1 durian (B1), and Ban 2 durian (B2) to generate biogas and methane. Using by the anaerobic digestion process, solid state. The results of the study found that the physical and chemical composition of durian peels of all 5 species are similar. and the potential to produce biogas from fermentation for 58 days. Chanee durian (CN) had the highest amount of accumulated biogas, equal to 1,019.32 mL/g-VS, followed by B2, KY, B1, and MT with the highest amount of biogas. Biogas accumulation was the least, equal to 906.96 mL/g-VS, and CN had the highest amount of accumulated methane gas, equal to 254.83 mL/g-VS, followed by B2, KY, B1, and MT had the least accumulated amount of methane gas, equal to 226.73. mL/g-VS It can be seen that durian peels have similar potential to produce methane gas. On average 50 percent.